Modelling local scour around bridge piers using TELEMAC - Kabir, Alamgir (Department of Civil Engineering, 2014)
Scour at bridge crossings is a major cause of bridge failure. There are several different types of scour such as general scour, constriction scour and local scour. One of the most serious types is local scour which occurs as a result of vortex formation around bridge piers and abutments (Hoffmans & Verheij, 1997; Raudkivi, 1998; Melville & Coleman, 2000; Richardson & Davis, 2001; Armitage & McGahey, 2003). Local scour is also one of the most difficult to predict accurately. If not adequately designed for, local scour of a riverbed at a bridge pier may become deep enough to undermine the pier foundation and eventually cause the bridge to collapse. Complete protection against scour is expensive and therefore not a favourable design option. It is generally cheaper to ensure that the foundation lies below the maximum expected scour depth. Traditionally, the maximum scour depth is predicted from empirical equations derived from simple laboratory tests without much regard for local conditions. Alternatively, smaIlscale hydraulic models, which are laborious and time intensive, are widely used. In view of the above, increasing attention is being paid to the use of Computational Fluid Dynamics (CFD) based modelling for the prediction of local scour and its opposite, local deposition. The ever-improving capabilities of computers and the increasing availability of powerful and flexible CFD codes have further assisted in this process. This study is a contribution in this direction.